The Innovation–Loyalty Nexus: Unpacking the Role of Perceived Quality in the Automotive Industry - Nabila; Dermawan, Rizky; Azhar, Ratih Mukti (CV. Lenggogeni Data Publishing, 2025)
This study investigates the effect of brand innovativeness on brand loyalty, with perceived quality as a mediating variable, in the context of Hyundai car consumers in West Java. Motivated by the highly competitive Indonesian automotive market where innovation is a key driver of customer retention, the research applies a quantitative design with purposive sampling of 120 respondents. Data were collected through an online survey and analyzed using Structural Equation Modeling with Partial Least Squares (SmartPLS). The results demonstrate that brand innovativeness significantly enhances both perceived quality and brand loyalty, while perceived quality exerts a positive effect on loyalty and mediates the relationship between innovativeness and loyalty. These findings underscore the strategic importance of continuous innovation complemented by improvements in after-sales service quality to reinforce Hyundai’s market position in an increasingly competitive environment.